GAMBARAN PENGETAHUAN SISWA SISWI KELAS XII IPA 1 DAN IPA 2 TENTANG HIV/AIDS DI SMAN 1 KUALUH HULU KABUPATEN LABUHAN BATU UTARA TAHUN 2015 - Endang Susilawati (Jurnal Online Keperawatan Indonesia, 2018)
About 50% new infection of Human Immunodeficiency Virus (HIV) in the world is adolescent as a consequences of lower understanding of adolescent about sex education. The objective of this researcih is to study the overview of knowledge of students of Grade XII of Natural Science 1 and 2 about HIV/AIDS at SMAN 1 Kualuh Hulu, Regency Labuhan Batu Utara in 2015.This research is a descriptive study aims to present the knowledge level of the student of SMAN 1 Kualuh Hulu. The population and sample in this research are student of Grede XII Natural Science 1 and 2 SMAN 1 Kualuh Hulu. The sample is 80 student using total sampling method.Based on this reserarch indicates that the student with good knowledge about HIV/AIDS is 45,0%, the sufficient knowledge for 27,5%, while without knowledge about HIV/AIDS is 16,3%.. therefore it is suggested to provide the student of SMAN 1 Kualuh Hulu with health education about HIV/AIDS in order to prevent the transmission of HIV/AIDS to the Adolescent and to increase the knowledge of student about HIV/AIDS.